Eimeria tenella Translation Initiation Factor eIF-5A That Interacts With Calcium-Dependent Protein Kinase 4 Is Involved in Host Cell Invasion - Liang, Shanshan; Dong, Hui; Zhu, Shunhai; Zhao, Qiping; Huang, Bing; Yu, Yu; Wang, Qingjie; Wang, Haixia; Yu, Shuilan; Han, Hongyu (Frontiers in Cellular and Infection Microbiology, 2021)
Eimeria tenella is an apicomplexan, parasitic protozoan known to infect poultry worldwide. An important calcium-dependent protein kinase (CDPK) has been identified in plants, green algae, ciliates and apicomplexan, such as E. tenella. CDPKs are effector molecules involved in calcium signaling pathways, which control important physiological processes such as gliding motility, reproduction, and host cell invasion. Given that CDPKs are not found in the host, studying the functions of CDPKs in E. tenella may serve as a basis for developing new therapeutic drugs and vaccines. To assess the function of CDPK4 in E. tenella (EtCDPK4), a putative interactor, translation initiation factor eIF-5A (EteIF-5A), was screened by both co-immunoprecipitation (co-IP) and His pull-down assays followed by mass spectrometry. The interaction between EteIF-5A and EtCDPK4 was determined by bimolecular fluorescence complementation (BiFC), GST pull-down, and co-IP. The molecular characteristics of EteIF-5A were then analyzed. Quantitative real-time polymerase chain reaction and western blotting were used to determine the transcription and protein levels of EteIF-5A in the different developmental stages of E. tenella. The results showed that the transcription level of EteIF-5A mRNA was highest in second-generation merozoites, and the protein expression level was highest in unsporulated oocysts. Indirect immunofluorescence showed that the EteIF-5A protein was found throughout the cytoplasm of sporozoites, but not in the refractile body. As the invasion of DF-1 cells progressed, EteIF-5A fluorescence intensity increased in trophozoites, decreased in immature schizonts, and increased in mature schizonts. The secretion assay results, analyzed by western blotting, indicated that EteIF-5A was a secreted protein but not from micronemes. The results of invasion inhibition assays showed that rabbit anti-rEteIF-5A polyclonal antibodies effectively inhibited cell invasion by sporozoites, with an inhibition rate of 48%.